Molecular sieve application in the recovery of Gaharu active marker compound from water mixture - Adam, Fatmawati; Abu Seman, M. N.; Chik, Syed M.Saufi Tuan; Tajuddin, Saiful Nizam (2016)
The essential oil of agarwood, which is known as Gaharu in Malaysia, is highly prized for its value for luxury fragrances and incense. However, the complexities of the chemical composition of agarwood are the primary challenge facing the establishment of an effective recovery method that can ensure uniform qualities and standards for each batch of essential-oil production. Although agarwood oil can be easily retrieved using the present hydro-distillation method, the high water solubility properties of a number of their key markers are the limiting factor for a proficient retrieval process. Regarding this problem, an elementary chemistry resolution study was performed on commercial agarwood essential oil-water mixture with the application of high performance liquid chromatography (HPLC) and fourier transforms infrared spectroscopy (FTIR). Interpretation of the results leads to a theoretical postulation that the agarwood water mixture consists of agarospirol, jinkohol, jinkoh eremol and kusenol. This study serves to identify the chemical characteristics of water-soluble agarwood compounds and to provide insight for researchers to develop a more strategic technique to improve their extraction process. In addition, this study is the groundwork on the ability of nano-sieve technique in the recovery of water soluble agarwood marker compounds from agarwood hydrosol. To achieve this purpose, a polypiperazine (PPA) and polyethlenesulfone (PES) based nanofiltration (NF) membrane were used. The effectiveness of this membrane on the separation of agarwood marker molecules was analysed and FTIR results showed that most of marker compounds (i.e. agarospirol, jinkohol, jinkoh eremol and khusenol) has been successfully separated from the aqueous agarwood. However, the performance of the membrane in terms of flux and permeability is quite low, which is 23.30 L/m2.h, with 6.76 L/m2.h.bar, respectively. The recovery of gaharu marker compound using membrane would help the local gaharu industry to improve the quality of gaharu essential oil.